DFT investigation of hydrogen atom-abstraction reactions of NHC-boranes by various carbon-centered radicals: barriers and correlation analyses. Issue 57 (18th September 2020) - Qu, Hong-jie; Yuan, Lang; Jia, Cai-xin; Yu, Hai-tao; Xu, Hui
Abstract : Correlation analyses were performed for understanding hydrogen-atom abstraction reactions. Abstract : In this study, we employed a quantum-mechanical computational method to investigate the hydrogen-atom abstraction reactions of two nitrogen heterocyclic carbene boranes (NHC-boranes), NHC-BH3 and NHC-BH2 CN, by a series of carbon-centered radicals bearing various substituents. We explored the degree of correlation of the activation and free energy barriers to their components. Furthermore, we also investigated the effects of the radical and substituent sizes, nucleophilicity/electrophilicity indices, and the spin density distribution of the radical reactants on the three fundamental barriers and the thermal contribution of the reaction energy to the kinetic barrier. Using the generated data, we assessed the abilities of the various radical reactants to abstract the hydrogen atom from NHC-boranes. Further, we performed a similar analysis after dividing those radical reactants into four groups, which were classified based on the dominant factor affecting their electronic density distribution, which involves the inductive effect, conjugation, hyperconjugation, and the feedback of lone-pair electrons. The results and conclusions of this investigation not only provide insight into the relationships between some of the key kinetic and thermodynamic parameters, which is useful for understanding the dynamics of such hydrogen-abstraction reactions, but also provide information for selecting suitable radical reactants for further experimental investigations.